2022
DOI: 10.1186/s40068-022-00246-8
|View full text |Cite|
|
Sign up to set email alerts
|

Spatiotemporal analysis of droughts characteristics and drivers in the Omo-Gibe River basin, Ethiopia

Abstract: Background Drought is one of the leading destructive natural disasters adversely affecting natural resources and livelihoods. Thus, this study evaluated the spatial and temporal meteorological drought characteristics and their drivers in the Omo-Gibe River basin (OGRB) from 1981 to 2017. The drought analysis used the standardized Precipitation Index (SPI) and the Standardized Precipitation Evapotranspiration Index (SPEI) with 4- and 12-month timescales. The Mann–Kendall (MK), Sen's slope estima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 61 publications
1
3
0
Order By: Relevance
“…Zeleke et al (2017) hand, identified 1984, 1987/1988, 1992/1993, 1999, 2003/2004 and 2007/2008 as the worst drought years in Ethiopia. Anose et al (2022) and Ayal et al (2021) in their respective paper found consistent results that agree with this paper. Furthermore, Mutsotso et al ( 2018) and Chitedze and Chikabvumbwa (2021) analyzed drought episodes by employing SPEI and SPI, respectively, in Kenya and Malawi.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Zeleke et al (2017) hand, identified 1984, 1987/1988, 1992/1993, 1999, 2003/2004 and 2007/2008 as the worst drought years in Ethiopia. Anose et al (2022) and Ayal et al (2021) in their respective paper found consistent results that agree with this paper. Furthermore, Mutsotso et al ( 2018) and Chitedze and Chikabvumbwa (2021) analyzed drought episodes by employing SPEI and SPI, respectively, in Kenya and Malawi.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, some studies recently investigated the spatiotemporal characteristics and trend of drought at the basin or sub-basin level in the country. Anose et al (2022) Getachew and Temesgen (2021) in the upper Awash River Basin and Yared et al (2015) in the upper Blue Nile Basin. These studies found more or fewer similarities in drought variability in their respective study regions.…”
Section: Introductionmentioning
confidence: 98%
“…Te spatial distribution of drought analysis is important for appropriate drought preparedness and early warning system development [27,[65][66][67]. Tere are several interpolation techniques to display drought-afected areas in ArcGIS software.…”
Section: Spatial Distribution Analysis Of Droughtmentioning
confidence: 99%
“…The SPEI is an improved index for regional drought monitoring because of its ability to identify the effects of temperature on dryness conditions [39]. The SPEI is mainly used to evaluate the role of temperature through its influence on potential evapotranspiration (PET), which relates to global warming and the occurrence of drought [40]. The SPEI is quantified using precipitation (P) and potential evapotranspiration (PET) as input variables, resulting in an index describing the water balance.…”
Section: Data Sourcesmentioning
confidence: 99%